2018
DOI: 10.5194/se-9-1437-2018
|View full text |Cite
|
Sign up to set email alerts
|

Formation of linear planform chimneys controlled by preferential hydrocarbon leakage and anisotropic stresses in faulted fine-grained sediments, offshore Angola

Abstract: Abstract. A new type of gas chimney exhibiting an unconventional linear planform is found. These chimneys are termed Linear Chimneys, which have been observed in 3-D seismic data offshore of Angola. Linear Chimneys occur parallel to adjacent faults, often within preferentially oriented tier-bound fault networks of diagenetic origin (also known as anisotropic polygonal faults, PFs), in salt-deformational domains. These anisotropic PFs are parallel to salt-tectonic-related structures, indicating their submission… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…Clausen et al (1999) have suggested that PF developed within a broadly polygonal array due to gravitational sliding influenced by far-field tectonic stresses, even if Wrona et al (2017) have recently suggested that such processes played no or an imperceptible role in the growth of this specific North Sea system. However, the hypothesis that layer-parallel displacements of these faults are accommodated by regional extension of the host strata has been confirmed in various basins, such as in the Lower Congo Basin (Gay et al, 2004) or in the Angola basin (Ho et al, 2018), and more recently by field studies showing that a radial extension may account for PFS development (Antonellini & Mollema, 2015;Petracchini et al, 2015).…”
Section: Polygonal Faults Orientations As a Marker Of Basin Extensionmentioning
confidence: 98%
See 4 more Smart Citations
“…Clausen et al (1999) have suggested that PF developed within a broadly polygonal array due to gravitational sliding influenced by far-field tectonic stresses, even if Wrona et al (2017) have recently suggested that such processes played no or an imperceptible role in the growth of this specific North Sea system. However, the hypothesis that layer-parallel displacements of these faults are accommodated by regional extension of the host strata has been confirmed in various basins, such as in the Lower Congo Basin (Gay et al, 2004) or in the Angola basin (Ho et al, 2018), and more recently by field studies showing that a radial extension may account for PFS development (Antonellini & Mollema, 2015;Petracchini et al, 2015).…”
Section: Polygonal Faults Orientations As a Marker Of Basin Extensionmentioning
confidence: 98%
“…> Classical normal faults usually propagate parallel to the principal stress σ1, while hydraulic fractures open in parallel to the intermediate horizontal stress σ2 and against the minimum principal stress σ3 (Cosgrove, 1995). However, PFS do not follow such behavior due to the anisotropy of unlithified cohesive fine-grained sediments and the anisotropic stress attributed to perturbations of the regional stress field can control the PF orientations (Ho et al, 2018). Volumetric contraction is a spontaneous process forming polygons by joints growing from an initiation point in all directions at the same time, such as in cooling lava flows (Aydin & DeGraff, 1988).…”
Section: Model Of Polygonal Faults In the Asymmetric Basin Of Grenadamentioning
confidence: 99%
See 3 more Smart Citations